Cell-free DNA test for pathogenic copy number variations: A retrospective study - Hong-Lei Duan; Jie Li; Wan-Jun Wang; David S. Cram; Wei Liu; Pei-Xuan Cao; Xiang-Yu Zhu; Ya-Li Hu (Elsevier, 2021)
Objective: To evaluate the detection rate (DR) by prenatal cell-free DNA test for pathogenic copy number variations (CNVs)＞2 Mb among pregnancies with fetal ultrasound abnormalities. Materials and methods: This was a retrospective study on 29 pregnant women with fetuses diagnosed as microdeletion/microduplication syndromes by prenatal chromosome microarray analysis (CMA). Cell-free DNA from the maternal plasma was sequenced on the NextSeq CN500 sequencer. The quality standard of unique map reads in a single sample was greater than 10 M and only gains and losses of more than 2 Mb were reported. Results: A total of 24 CNVs were identified by cell-free DNA test among the 21 fetuses with pathogenic CNVs identified by prenatal CMA, including 20 consistent CNVs and 4 inconsistent CNVs. Overall, the DR of cell-free DNA test for pathogenic CNVs ＞2 Mb was 69%. Microdeletions or microduplications at 22q11.2 were the most common CNVs, with a DR of 4/5 (80%) and 3/4 (75%) respectively. Conclusion: Cell-free DNA test exhibited a moderate DR for pathogenic CNVs ＞2 Mb among fetuses with ultrasound abnormalities. Cell-free DNA test could provide an opportunity for early screening before the appearance of abnormalities on fetal ultrasound, while further clinical data and cost-effectiveness assessment are needed.